The Zondervan NIV Bible commentary : v. 2 - Barker, Kenneth L.; Kohlenberger, John III (Grand Rapids, MI Zondervan, 1994)
Contents : v. 2 : New Testament. Includes indexes, pictures, maps and charts
An abridgement of The expositor's Bible commentary, retaining the interpretative material but missing the text of the NIV and the detailed scholarly notes and discussions
Keywords: Bible. N.T. -- commentaries